The Role of Regulatory Compliance in Shaping Risk Management Practices in Kuwaiti Insurance Companies - Alibrahim, Noora F.; Malick, Shahroz Saeed (Issues in Economics and Business, 2024)
The paper examines the issues construed by the insurance organizations in the State of Kuwait, through changing the policies and regulations. It also shows the hazard of non-compliance and how that could affect risk management strategies. This research is conducted via a survey-based methodology where structured questionnaires are used to shed light on the interplay of regulatory requirements with the implementation and success of risk management strategies in the insurance sector of Kuwait. Data has confirmed the expected, indicating the correlation between the level of regulatory query strictness and business awareness of the risks. Moreover, the paper indicates a direct positive impact of robust regulation and risk management measures. Thus, the research shows that strong regulatory environment matters a lot in optimal risk management. Finally, this research provides knowledge to the subject literature that accentuates the fact that the role of regulatory measures upon which the companies can use in developing organizational behavior is more paramount than risk management decisions. The research fits well, since it emphasizes the role of knowing how the regulating stringency and risk management processes are linked, which is usually in a rapidly changing regulatory landscape. While insurance companies in Kuwait become more innovative and invent the new ways of complying to the oversight agencies to use good governance and sound risk management strategies, the insights mentioned above become crucial.